Organizational commitment and intention to leave among nurses: The mediating role of moral obligation - Omar, Khatijah; Mohamed Anuar, Marhana; Abdul Majid, Abdul Halim; Johari, Husna (Universiti Utara Malaysia Press, 2012)
In today’s fast-paced economic competition, committed and loyal employees are important for the profit-oriented organizations to gain and sustain their competitiveness.Even for non-profit-oriented organizations like hospitals and universities, these committed and loyal employees will lead to better quality service and improved organizational performance.Thus, it is vital for the organizations to sustain employees’ commitment because once the employees’ commitments decrease, it would be difficult for organizations to retain their employees. This study investigated the relationship between organizational commitment and intention to leave among nurses in Malaysian public hospitals, and determined the role of moral obligation as a mediator on the relationship between organizational commitment and intention to leave.The study focused on permanent nurses working in public hospitals in Peninsular Malaysia. The results supported that organizational commitment was significantly and negatively related to intention to leave.The macro results also showed that moral obligation was a mediator in the relationships between organizational commitment and the intention to leave.The results were crucial to be looked into so that management and employers could have ample understanding and guidelines if they were to draft retention strategies.Even though many studies had been conducted on the intention to leave, most of them were conducted in developed countries and this study is believed to enhance the literature gap since it has an emphasis in the Malaysian context